STRATEGI KEPALA DESA SRIKATON DALAM UPAYA PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN OBJEK WISATA - Yessy Destiani (Jurnal Progress Administrasi Publik, 2022)
The existence of villages in Indonesia is quite a lot, which is accompanied by various complexities of problems and obstacles in it. Circumstances like this illustrate that the heavier the burden of the village head to empower the people of his village. The purpose of this research is to find out the strategy carried out by the Head of Srikaton Village to empower the community through the development of tourist attractions. The birth of the tourist village encouraged various village heads to explore the tourism potential possessed by his village by introducing the characteristics possessed by his village to realize the independence of the village. Â  Keywords: Village headÂ  strategy, Tourism object development